2022
DOI: 10.1371/journal.pcbi.1009978
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the best time interval between doses in a two-dose vaccination regimen to reduce the number of deaths in an ongoing epidemic of SARS-CoV-2

Abstract: The SARS-CoV-2 pandemic is a major concern all over the world and, as vaccines became available at the end of 2020, optimal vaccination strategies were subjected to intense investigation. Considering their critical role in reducing disease burden, the increasing demand outpacing production, and that most currently approved vaccines follow a two-dose regimen, the cost-effectiveness of delaying the second dose to increment the coverage of the population receiving the first dose is often debated. Finding the best… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…However, we see in the other results that, as soon as one increases the number of doses available, one strategy begins to be significantly more beneficial than others. These results are supported by the findings in [17] .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, we see in the other results that, as soon as one increases the number of doses available, one strategy begins to be significantly more beneficial than others. These results are supported by the findings in [17] .…”
Section: Discussionsupporting
confidence: 89%
“…Ferreira et al [17] also demonstrated that first dose efficacy and availability are essential parameters when considering the optimal interval between doses, whereas varying values of infection transmission (effective reproduction number) did not impact estimates. This was also observed in our study, supporting our choice of using various scenarios with fixed probabilities of infection over the time horizon of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we need to pay attention to the possibility that some risk factors, such as obesity, diabetes and cancer, may still affect the clinical outcomes of patients [ 36 , 37 ]. In addition, vaccines may differ in protective efficacy, but two-dose vaccination could still significantly reduce the risk of new SARS-CoV-2 infection [ 38 , 39 ]. With the evolution of the SARS-CoV-2 virus, the protective effect of existing vaccines may be reduced, specific vaccine design for different mutant strains may be the focus in the future [ 31 ].…”
Section: Discussionmentioning
confidence: 99%